TERAPI RELAKSASI AUTOGENIK UNTUK MENURUNKAN NYERI POST OPERASI TURP PADA PASIEN BPH - Hati, Yulis; Muchsin, Rosanti; Tamara, Boby (Jurnal Keperawatan Priority, 2023)
Benign Prostatic Hyperplasia (BPH) is a benign tumor that often affects men, and its incidence increases with age, namely over 40 years. TURP is a solution for treating BPH, in the postoperative TURP effects patient will feel pain. Autogenic relaxation technique which is a part of non-pharmacological pain management. This study aims to determine the effect of autogenic relaxation therapy on patient pain in postoperative TURP BPH in the ICU room of Sri Pamela Tebing Tinggi Hospital in 2022. This research is a quantitative study with a pre-experimental approach. The population is 150 people with a sample using a purposive sampling technique totaling 75 people. The results of the study showed that before the Autogenic Relaxation was carried out it was 2.80 after the Autogenic Therapy was carried out the average value of the pain scale was 2.44. This means that there is an average decrease in the Pain Scale of 0.36. Based on the results of the paired t-test, it was found that there was an effect of autogenic therapy on the pain scale of postoperative TURP BPH patients with a p-value of 0.001 <a = 0.05. It is suggested that RS Sri Pamela Tebing Tinggi informs the importance of implementing autogenic relaxation techniques to reduce the pain scale in postoperative TURP BPH patients.